Digital Supplier Selection for a Garment Business Using Interval Type-2 Fuzzy TOPSIS - ÖZBEK, AHMET (EGE UNIV, 2020)
The aim of this study was to use the interval type-2 fuzzy TOPSIS method to select the best supplier among a number of suppliers digitized by Industry 4.0 for a company operating in the garment industry. The interval type-2 fuzzy TOPSIS method involves an interval of type-2 fuzzy sets and can model uncertainties very well to solve fuzzy multi-criteria decision making problems. Alternatives were listed based on closeness indexes, and the best digital supplier was selected based on sensitivity analysis. This is the first study to use the model in question to select the best digital supplier for a company. We, therefore, believe that it will contribute to the literature. It is recommended that the model in question be used in other industries as well.
Keywords: Industry 4.0; Digital Supply Chain; Fuzzy TOPSIS; Garment Industry; THINGS IOT; CHAIN; METHODOLOGY; LOGISTICS; FRAMEWORK; INTERNET; IMPACT; MODEL; MCDM